Behaviour of Listeria monocytogenes in Lighvan cheese following artificial contamination during making, ripening and storage in different conditions. (15th November 2016) - Moosavy, Mir‐Hassan; Esmaeili, Saber; Mortazavian, Amir Mohammad; Mostafavi, Ehsan; Habibi‐Asl, Bohlol; Hosseini, Hedayat; Khatibi, Seyed Amin
Abstract : This study investigated the behaviour and fate of Listeria monocytogenes at different ripening temperatures and NaCl concentrations in traditional Lighvan cheese. L. monocytogenes was added to raw sheep's milk. After producing the cheese, they were stored in 8%, 12% and 15% NaCl at 4, 9 and 14 °C. Sampling was performed for 150 days. Different temperature and NaCl concentrations had a significant effect on the survival of L. monocytogenes ( P  <   0.001). The lowest growth and survival rates of L. monocytogenes were in 15% NaCl at 14 °C and 12% NaCl at 14 °C, respectively. Also, the highest growth and survival rates of the bacterium were in 8% NaCl at 4 °C.